1957
DOI: 10.1149/1.2428469
|View full text |Cite
|
Sign up to set email alerts
|

Closure to “Discussion of ‘Oxidation of Copper to Cu[sub 2]O and CuO’ [D. W. Bridges, J. P. Baur, G. S. Baur, and W. M. Fassell, Jr. (pp. 475–478, Vol. 103)]”

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
2

Year Published

1974
1974
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 0 publications
5
37
2
Order By: Relevance
“…According to the literature results for copper oxidation, [3][4][5][6][7] it is generally accepted that the growth of Cu 2 O is predominant at 873-1173 K. The rate-determining step in this temperature range is the outward diffusion of copper in Cu 2 O, as agrees well with Wagner's scaling theory. 8) Moreover, simultaneous lattice diffusion and grain boundary diffusion have been found to be responsible for the growth of Cu 2 O in this higher temperature range.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…According to the literature results for copper oxidation, [3][4][5][6][7] it is generally accepted that the growth of Cu 2 O is predominant at 873-1173 K. The rate-determining step in this temperature range is the outward diffusion of copper in Cu 2 O, as agrees well with Wagner's scaling theory. 8) Moreover, simultaneous lattice diffusion and grain boundary diffusion have been found to be responsible for the growth of Cu 2 O in this higher temperature range.…”
Section: Introductionsupporting
confidence: 69%
“…intermediate temperatures Some studies 5,17,18) showed that the thin CuO film for copper oxidation at and above 873 K is impervious to oxygen, and the oxygen potential at the Cu 2 O/CuO interface is determined by the dissociation pressure of CuO, which is constant at a given temperature. However, few works have been done to investigate the case at lower temperatures.…”
Section: Oxygen Pressure Dependence Of Activation Energy Atmentioning
confidence: 99%
“…According to a number of studies [4][5][6][7][8], the oxidation of copper follows the parabolic law of Pilling and Bedworth:…”
Section: Results Of Measurements Of the Kinetics Of Copper Oxidationmentioning
confidence: 99%
“…It has been concluded by numerous studies that while the rate of copper oxidation was increased with increasing temperature, oxygen pressure had no effect on the rate when the pressure is above the equilibrium potential for Cu/CuO. 1,2) Plascencia et al studied copper oxidation in the temperature range of 300-1 000°C. It showed that the oxidation was followed by logarithmic law of surface diffusion at 300-500°C, and by parabolic law of diffusion of copper ions through oxide layer at 600-1 000°C.…”
Section: Introductionmentioning
confidence: 99%